Husband’s knowledge, attitude and behavioural disposition to wives screening for cervical cancer in Ibadan (2014)
Cervical cancer is one of the leading causes of cancer death in women from both developed and developing countries of the world. About half a million new cases are seen worldwide each year, most occurring in developing countries where cervical cancer screening and treatment are less available and accessible. Several studies have identified various barriers to cervical screening in sub-Saharan African countries which may account for why only a few women are screening. This study aimed at assessing husbands’ cervical cancer related knowledge, attitude and practices encouraging their wives to screen for cervical cancer in Ibadan. Through a descriptive survey design, A self-developed validated instrument on Husbands’ Disposition to Cervical Cancer Screening (HDCCS) was used for data collection based on random sampling. Four research questions were raised in the study. Data collected was analyzed using Pearson Product Moment Correlation. Descriptive statistics indicated that 70% of the husbands had good cervical cancer related knowledge. On attitude to screening, 55.1% of the husbands will encourage their wives to screen for cervical cancer if they knew a test that can detect cervical cancer early. Husbands’ behaviour encouraging wives to screen indicates that wives of 55.2% of the husbands have not gone for pap smear test, 89.1% of husbands did not know when their wives should go for pap smear test and 80% did not remind their wives to go for pap smear test Correlation analysis showed that husbands’ cervical cancer related knowledge had a significant linear relationship with husbands’ practices encouraging wives to go for cervical cancer screening while their attitude towards screening did not. It was concluded that there is need to educate husbands about cervical cancer and the need for their wives to screen before symptoms are noticed.